Spiritual well-being and hope in the preoperative period of cardiac surgery - Simone Maria Muniz da Silva Bezerra; Eduardo Tavares Gomes; Paulo César da Costa Galvão; Karolayne Vieira de Souza
ABSTRACT Objective: To characterize relations between spiritual well-being and hope of patients in the preoperative period of cardiac surgery. Method: Exploratory cross-sectional study with quantitative approach, performed in the infirmaries of a reference hospital in cardiology. We evaluated 69 patients hospitalized in preoperative period of myocardial revascularization, valve repair or replacement. Results: We verified that patients hold relevant scores of hope and welfare in all areas, being the existential well-being significantly lower than the religious one. The average of the spiritual well-being score was below the required to be considered high. There was no significant correlation between welfare and hope. Conclusion: Nurses should develop a watchful eye to these issues, be trained in specific protocols of spiritual anamnese and use the real moments of care to strengthen the patients.